The Influence of Perceived Medication Necessity, Medication Concern, Patient-Healthcare Provider Communication, and Complexity of Medical Regimens on Medication Adherence in Patients with Acute Coronary Syndrome after Hospitalization - เพ็ญพิมล, ปัณฑิตา; เจริญกิจการ, วิชชุดา; วัฒนกิจไกรเลิศ, ดวงรัตน์; ทุมวิภาต, ฉัตรกนก (Journal of The Royal Thai Army Nurses, 2024)
การวิจัยเชิงทำนายครั้งนี้มีวัตถุประสงค์เพื่อศึกษาปัจจัยด้านการรับรู้ความจำเป็นต่อการรับประทานยา ความกังวลจากการรับประทานยา การสื่อสารระหว่างผู้ป่วยและบุคลากรทางการแพทย์และความซับซ้อนของการใช้ยาตามแผนการรักษา ต่อความสม่ำเสมอในการรับประทานยาของผู้ป่วยภาวะหัวใจขาดเลือดเฉียบพลันภายหลังได้รับการจำหน่ายออกจากโรงพยาบาล จำนวน 120 คน วิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณนา สัมประสิทธิ์สหสัมพันธ์แบบสเปียร์แมน และสถิติการวิเคราะห์ถดถอยโลจิสติก ผลการศึกษาพบว่า ผู้ป่วยภาวะหัวใจขาดเลือดเฉียบพลันมีความสม่ำเสมอในการรับประทานยาร้อยละ 60 ปัจจัยทั้ง 4 ด้านดังกล่าวเบื้องต้นสามารถทำนายความผันแปรของความสม่ำเสมอในการรับประทานยา ได้ร้อยละ 17.7 (Nagelkerke R2 = .177, p < .05) โดยการรับรู้ความจำเป็นต่อการรับประทานยา สามารถทำนายความสม่ำเสมอในการรับประทานยาได้อย่างมีนัยสำคัญทางสถิติ (OR = 1.242, 95%CI = 1.084 - 1.422; p = .002) ผู้วิจัยเสนอแนะว่า พยาบาลควรส่งเสริมการให้ข้อมูลเรื่องความจำเป็นของการรับประทานยา เพื่อส่งเสริมความสม่ำเสมอในการรับประทานยา The Influence of Perceived Medication Necessity, Medication Concern, Patient-Healthcare Provider Communication, and Complexity of Medical Regimens on Medication Adherence in Patients with Acute Coronary Syndrome after Hospitalization This correlational predictive design research aimed to study factors predicting medication adherence in patients with Acute Coronary Syndrome (ACS) after hospitalization. A sample of 120 patients was selected by convenience. The data were analyzed by using descriptive statistics and logistic regression analysis. The findings showed overall medication adherence 60%. Perceived medication necessity, medication concern, patient-healthcare provider communication, the complexity of medical regimens could be explained by medication adherence using logistic regression which accounted for 17.7% of the variance (Nagelkerke R2 = .177, p < 0 .05). Perceived medication necessity could significantly predict medication adherence (OR = 1.242, 95%CI = 1.084-1.422; p = .002). With these findings, it is recommended that nurses should promote a medication adherence by provide details and explanations on the necessity and benefits of ACS medications.